Corrosion Inhibition Effect of 4-(2-Diethylamino-Ethylsulfonyl)-Phthalonitrile and 4,5-Bis(Hexylsulfonyl)-Phthalonitrile - Esma Sezer; Belkis Ustamehmetoğlu; Zehra Altuntaş Bayır; Kerim Çoban; Ayfer Kalkan (International Journal of Electrochemistry)
Inhibition of stainless steel corrosion in a 3.0 M NaCl solution by 4-(2-diethylamino-ethylsulfanyl)-phthalonitrile (DAESPN) and 4,5-bis(hexylsulfonyl)-phthalonitrile (Bis-HSPN) was investigated by polarization and electrochemical impedance spectroscopy (EIS) measurements. The values of cathodic (βc) and anodic (βa) Tafel slopes, 𝑖corr, 𝐸corr, corrosion rate (CR), and inhibition efficiences (IE%) obtained from polarization curves and polarization resistance (𝑅P), double-layer capacitance (𝐶dl), specific capacitance (𝐶sp) values were obtained from EIS. Double-layer capacitance differences in the presence and absence of inhibitors were also obtained from EIS measurements as suggested in the literature in order to investigate the interaction of them with metal surface. Results show that both DAESPN and Bis-HSPN are effective in cathodic reaction. Impedance measurements suggest higher surface coverage for DAESPN. The interaction between the inhibitor and the stainless steel was investigated by the adsorption isotherm. Langmuir adsorption isotherm 𝐾ads was applied and Δ𝐺 values were obtained and found as 4.32×10−4, 1.17×10−4 and 9.2 kJ, 12.5 kJ for DAESPN and Bis-HSPN, respectively, which suggests the electrostatic interaction between charged metal surface and charged organic molecules.